(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Vasomotor rhinitis is one of the most common diseases in economically developed countries. In recent decades, among diseases of the upper respiratory tract, there has been an increase in the prevalence of vasomotor rhinitis in all age groups of the population. It is known that vasomotor rhinitis very often occurs in association with diseases of other organs and systems of the body. The problem of diagnosis and treatment of upper respiratory tract diseases in patients with endocrine pathology is one of the least studied areas of modern otolaryngology.